ENT 530 Case Study: Smokey Tea / Nur Aina Nadiah Mohammad Akmal ... [et al.] - Mohammad Akmal, Nur Aina Nadiah; Abdul Rahman, Nur Afifah; Ismail, Hafizul Hakim; Zaharuddin, Luqman Hakeem; Md Zuber, Muhammad Zulfadhli Syam; Badrul Hisham, Mohammad Fahmie; Shaffian, Nur Muhammad Alwaliaddin (2021)
Smokey Tea is a beverages brand that sells ready-to-drink products. This product was founded by Hasrizal Hamar in 2018. The first product for Smokey Tea is known as The Tarik Gula Karamel. It is started in the Anak Raub Restoran and the Restoran Patin Temerloh, Shah Alam. In the beginning, only 1 flavor was released and packed in a bottle. The product was responded very well by customers. After that, they released a brand new flavor which is hazelnut, Preto, banana, and ginger. They also promote their products on social media such as Facebook and Instagram as their main platform. To further expand the sales of these products, they are opening up space to agents and dropships. However, their sales did not get much response due to some problems. Especially, lack of graphic design in the advertisement, lack of knowledge in marketing, and inappropriate target audiences. As we all know, for small businesses to produce this ready-to-drink product uses a lot of capital, especially in production. However, the problemcan be curbed if they analyze it more deeply and overcome the problem. There are many problems that Smokey Tea can improve their business to avoid losses, to compete with other competitors.